HUBUNGAN PENGASUHAN ORANG TUA MENGHADIRI KEGIATAN SEKOLAH PERTEMUAN DENGAN TINGKAT PEMBELAJARAN SISWA PADA GURU DI SEKOLAH - Safari Safari (Akademika, 2021)
The main objective of this study is to determine whether there is a relationship between the level of concern of parents attending school activity meetings with the level of student learning pleasure with teachers at school. The design used in this study is quantitative research. The data in this study used data from the AKM 2020 SMA / SMK test results held by Pusmenjar. The population of this study is the condition of the level of pleasure of students studying with teachers at school in SMA / SMK students who are studying with teachers at school in 2020, while the sample is the condition of the level of feelings of SMA / SMK students who are taking the 2020 AKM test. The data in this study In the form of a questionnaire that was answered by 269988 SMA / SMK students participating in the 2020 AKM (514 districts / districts in 34 provinces in Indonesia). Based on the results of simple regression analysis, the following results were obtained. Statistically, there is a positive relationship between the level of parental concern in attending school meeting activities and the level of pleasure of students learning with teachers at school. (P <0.05) although the contribution is relatively small, namely 1% and the regression equation is Y = 2.663 + 0.120X. The conclusion is that there is a relationship between the level of parental care attending school meeting activities with the level of student learning pleasure with teachers at school (P <0.05).